Intelligent Hydrogel Actuators With Controllable Deformations and Movements - Zhao, Qian; Yu, Zhenglei; Liang, Yunhong; Ren, Lei; Ren, Luquan (Frontiers in Materials, 2021)
The near infrared laser driven intelligent hydrogel actuator systems including printable N-isopropylacrylamide-nanosized synthetic hectorite clay-nanofibrillated cellulose hydrogels and N-isopropylacrylamide-4-hydroxybutyl acrylate-nanofibrillated cellulose hydrogels with high response rate were prepared via 3D printing and hydrothermal synthesis, respectively. The addition of nanofibrillated cellulose was beneficial for rheology improvement. The 3D printing intelligent hydrogel actuators with structure patterns of Model I and II exhibited saddle and inverted saddle deformations respectively, proving the validity of 3D printing. In order to improve response rate and enrich movement patterns, hydrothermal synthesis intelligent hydrogel actuators were prepared on the base of 3D printing intelligent hydrogel compositions. The addition of nanofibrillated cellulose maintained the controllable near infrared laser response. Based on wedge-shape design, the hydrothermal synthesis intelligent hydrogel pushed the resin ball with weight of 130 mg forward 8 mm in 39 s. By changing the torque values of hydrogel on different direction, the actuator realized controllable continuous rollover movement. Attributed to the longilineal shape, the intelligent hydrogel actuator reached effective displacement of 20 mm in 10 s via the forward movement. The hydrogel material characteristics and structure design significantly realized the multiple controllable functional 4D printing deformations and movements. The combination of advantages of 3D printing and hydrothermal synthesis intelligent hydrogels provided a new development direction and abundant material candidates for practical applications of 4D printing in soft robot, information sensing and health engineering.